An Attribute Involved Non deterministic Cryptosystem using Composite Residuosity Class Problem - Gunnala, Sumalatha; Murthy, D.S.R; Kakarla, Shirisha (International Journal of Computer Sciences and Engineering, 2025)
In this paper, we design a public key encryption scheme, is based on the composite residuosity classes and having the property as randomization, also called as non- determinism. The non-deterministic nature of this cryptosystem produces dissimilar ciphertexts for a given same plaintext character on each iteration. The intractability of factorization of this scheme is achieved through the concept of composite residuosity class problem. The key involved in the encryption procedure of the scheme uses the credentials like unique identities of the sender to ensure the authenticity of the user. These identities, are also called attributes of the user, include email, Social Security Number (SSN) or Aadhaar number etc. While encrypting the message, the sender will use any of his identity value as a key in the procedure. The recipient can calculate this attribute value in the decryption procedure